Effect of Twin Circular Underground Voids on Bearing Capacity of Strip Foundations (European Journal of Engineering Science and Technology, 2024)
Underground voids can significantly alter the stress and strain conditions of the surrounding soil mass, consequently affecting the stability of buildings located on the surface. Numerous numerical and experimental methods have been employed to investigate the effects of voids on nearby structures. In this research, a mixed lower bound-finite element method is utilized to study the stability of strip foundations situated above twin continuous voids. The soil behavior is modeled using the Mohr-Coulomb yield function along with an associated flow rule. Three-noded triangular stress elements are used to mesh the stress field, considering stress discontinuities at the common edges of adjacent elements. The study assumes that the two voids are identical in terms of radius, distance from the footing centerline, and depth from the ground level. The primary geometrical parameters considered in the analysis are the location and radius of the voids, as well as the strength parameters of the soil. By investigating the changes in bearing capacity concerning these factors, practical charts are proposed to aid in understanding the stability of the foundation. The results of the current study reveal the existence of an unsafe zone beneath the foundations, where the impact of the twin voids on bearing capacity reduction can be significant. Understanding these effects is crucial for design and construction of structures in areas prone to underground voids and also to decide where to bore infrastructure tunnels in order to have minimum effect on stability of the above buildings.